2017
DOI: 10.3923/jms.2017.102.106
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacists-led Drug Information Service in a Tertiary Care Hospital in India

Abstract: is an International, peer-reviewed scientific journal that publishes original article in experimental & clinical medicine and related disciplines such as molecular biology, biochemistry, genetics, biophysics, bio-and medical technology. JMS is issued four times per year on paper and in electronic format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…10 A study conducted in a tertiary hospital in India reported interns to be the most frequent seekers of DIS followed by nurses. 11 Also, another study in India showed nurses to be the most frequent seekers of DIS compared to other health professionals. 5 An Ethiopian study reported pharmacists to be the most frequent users of DIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A study conducted in a tertiary hospital in India reported interns to be the most frequent seekers of DIS followed by nurses. 11 Also, another study in India showed nurses to be the most frequent seekers of DIS compared to other health professionals. 5 An Ethiopian study reported pharmacists to be the most frequent users of DIS.…”
Section: Discussionmentioning
confidence: 99%
“…2 Another study in India reported the most asked drug information to be drug indication, followed by side effects of drugs. 11 Drug information most commonly sought from hospital pharmacists were; drug dosage, drug interactions, side effects of drugs and drug use in pregnancy. However, the most frequently requested from community pharmacists were cost of drugs, drug dosage and drug substitutes respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For that matter, DIC should have adequate resources and specifically qualified professionals such as pharmacists, who can provide impartial and relevant information in response to the inquiries. 13 Users can reach out to the centre by phone, in person, by fax, or through e-mail, and their queries will be answered verbally or in a structured written format. 14 …”
Section: Discussionmentioning
confidence: 99%
“… 20 By providing drug information services, pHarmacists assist the medical practitioner and other HCPs in individualizing patient therapy by pharmaceutical care or a group of patients as part of a disease management programme. 13 …”
Section: Discussionmentioning
confidence: 99%
“…So, the idea of a mobile application software might meet the need of the hour. 61 Further, DIC can be involved in research by encouraging young researchers in the field of pharmacoepidemiology, pharmacoeconomics and rational use of therapy. 21 Twenty-four hours DI services can be planned at the national level meeting the increased need throughout the country at low cost.…”
Section: Future Perspectivesmentioning
confidence: 99%